2017
DOI: 10.1021/acs.jpca.7b07635
|View full text |Cite
|
Sign up to set email alerts
|

Theory of First Order Chemical Kinetics at the Critical Point of Solution

Abstract: Liquid mixtures, which have a phase diagram exhibiting a miscibility gap ending in a critical point of solution, have been used as solvents for chemical reactions. The reaction rate in the forward direction has often been observed to slow down as a function of temperature in the critical region. Theories based upon the Gibbs free energy of reaction as the driving force for chemical change have been invoked to explain this behavior. With the assumption that the reaction is proceeding under relaxation conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Snyder and Eckert measured the rate of the Dieles–Alder reaction of isoprene with maleic anhydride in critical binary solutions (binhexane/nitrobenzene, hexane/nitroethane) and found that the reactions accelerated 30–40% near the critical point. Baird et al . investigated the rates of various reactions in different critical binary solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Snyder and Eckert measured the rate of the Dieles–Alder reaction of isoprene with maleic anhydride in critical binary solutions (binhexane/nitrobenzene, hexane/nitroethane) and found that the reactions accelerated 30–40% near the critical point. Baird et al . investigated the rates of various reactions in different critical binary solutions.…”
Section: Introductionmentioning
confidence: 99%